Peningkatan Kinerja Organisasi melalui Pemberdayaan Sumber Daya Manusia, dan Perubahan Organisasi (Studi pada Industri Jasa di Jawa Timur) - Boge Triatmanto (Jurnal Aplikasi Manajemen, 2012)
Objectives of the research were to examine and prove empirically the influence of human resources empowerment, directly and indirectly toward performance, through organization change. Objectives of the research in detail were to analyze and examine empirically the influences of: (1) human resources empowerment on organization performance, (2) human resources empowerment on organization change, (3) organization change on organization performance. Population of the research was 69 starr hotels, which spread over the East Java Province. 34 hotels were taken as samples. The respondents were 216 managers. Samples were taken using proportional sampling method and data analysis of the research used SEM (Structural Equation Model). The main finding of this research was that the organization performance would be enhanced if the human resources were empowered in participating to achieve the organization goal, commit to the organization, and have greater authority and responsibility in decision-making process. Human resources empowerment has insignificant influence on the organization change.Keywords: Human Resources Empowerment, Organization performance, Organization change.